Effect of prodigiosin on the alleviation of the intestinal inflammation of weaned rats based on 1H-NMR spectroscopy study and biochemistry indexes (Brazilian Journal of Pharmaceutical Sciences, 2019)
Weaning results in intestinal dysfunction, mucosal atrophy, transient anorexia, and intestinal barrier defects. In this study, the effect of prodigiosin (PG) on the intestinal inflammation of weaned rats was investigated by using 1 H-NMR spectroscopy and biochemistry indexes to regulate the intestinal metabolism. After administration for 14 days, the body mass of the PG group was increased by 1.29‑ and 1.26-fold compared with those of the control and alcohol groups, respectively, using a dose of 200 μg PG·kg-1 body weight per day. PG increased organic acid content and decreased moisture, pH values, and free ammonia in feces. In addition, PG alleviated the intestinal inflammation of weaned rats. The analysis of 1 H-NMR signal peak attribution and the model validation of metabolic data of feces contents showed that PG significantly affected the metabolism of small molecular compounds in the intestinal tract of weaned rats. This study presents the promising alternative of using PG to alleviate intestinal inflammation effectively in the intestinal tract of weaned rats.